Fatigue effect on landing biomechanics among individuals with anterior cruciate ligament reconstruction: a systematic review - Woddillah, Nurul Ain; Azhar, Noor Izzati; Manaf, Haidzir; Justine, Maria; Alfawaz, Saad S; Munajar @ Munajat, Munayati; Bukry, Saiful Adli (Faculty of Medicine, Universiti Malaya, 2023)
It is well established that knee stability can be altered during fatigue, which may increase the risk of anterior cruciate ligament (ACL) injury. This is due to a reduction in neuromuscular control that leads to abnormal movement patterns. This study aims to review the impact of fatigue on landing biomechanics among individuals who have undergone anterior cruciate ligament reconstruction. Four databases (Scopus, EBSCO, Web of Science, and Google Scholar) were searched for relevant articles, with a focus on full-text English-language research articles published between 2012 and 2022. The quality of the included studies was evaluated using the McMaster Critical Review Form for Quantitative Studies, and two independent reviewers were involved in the study evaluation, with a third reviewer resolving any discrepancies. Data on study demographics, fatigue simulation methods, landing tasks, outcome measures, and results were extracted from included studies. Eight studies met the inclusion criteria and were included in the analysis. The results of these studies showed that fatigue simulation reduced knee flexion only in two studies and increased hip flexion moment only in two studies during landing among individuals with ACLR. These inconclusive results show that fatigue may negatively impact landing biomechanics in people who have had an ACLR, potentially increasing their risk of re-injury. Fatigue did not affect the landing strategies adopted by individuals who have undergone ACLR. Some of these changes, such as reduced knee flexion and reduced hip flexion moment, could potentially increase the risk of re-injury. However, other changes, such as an increased hip flexion angle, may protect the joint from further injury. More research is needed to better understand the impact of fatigue on landing strategies in this population and to identify strategies that can minimize the risk of re-injury.